1997
DOI: 10.1046/j.1365-2141.1997.192707.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptives and venous thrombosis: different sensitivities to activated protein C in women using second‐ and third‐generation oral contraceptives

Abstract: Summary.Epidemiological studies have shown that women who use third-generation oral contraceptives (OC) containing desogestrel, gestodene or norgestimate have a higher risk of venous thrombosis than women who use second-generation OC containing levonorgestrel. It is also known that a mutation in factor V (factor V Leiden ), which results in resistance to activated protein C (APC) and which is the most common cause of hereditary thrombophilia, potentiates the prothrombotic effect of OC.Effects of APC on thrombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
265
2
5

Year Published

1998
1998
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 319 publications
(298 citation statements)
references
References 29 publications
26
265
2
5
Order By: Relevance
“…Table I summarizes the data together with the results for men and women, separately. In both tests women appeared slightly more resistant to APC than men, confirming earlier reports (De Stefano et al, 1996;Henkens et al, 1995;Koster et al, 1993;Rosing et al, 1997), but only in the ETP-based assay did the gender difference reach statistical significance (P < 0·05, Table I). Fig 2 and Table II summarize the effects of OC use on nAPCsr obtained in both tests for plasmas of normal healthy women who do not carry the factor V Leiden mutation and of women heterozygous for the factor V Leiden mutation.…”
Section: Comparison Of Apc Sensitivity Ratios Of Normal Individuals Asupporting
confidence: 78%
See 2 more Smart Citations
“…Table I summarizes the data together with the results for men and women, separately. In both tests women appeared slightly more resistant to APC than men, confirming earlier reports (De Stefano et al, 1996;Henkens et al, 1995;Koster et al, 1993;Rosing et al, 1997), but only in the ETP-based assay did the gender difference reach statistical significance (P < 0·05, Table I). Fig 2 and Table II summarize the effects of OC use on nAPCsr obtained in both tests for plasmas of normal healthy women who do not carry the factor V Leiden mutation and of women heterozygous for the factor V Leiden mutation.…”
Section: Comparison Of Apc Sensitivity Ratios Of Normal Individuals Asupporting
confidence: 78%
“…Acquired APC resistance particularly occurs in plasma of women who use oral contraceptives (Henkens et al, 1995;Olivieri et al, 1995;Rosing et al, 1997) or who are pregnant (Meinardi et al, 1997) and is particularly observed in a functional test in which the ability of APC to down-regulate coagulation is quantitated by measuring its effect on thrombin generation initiated in plasma via the extrinsic pathway .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, although OCP use causes overall hypercoagulability, a well-known fact, our study shows that the variable effects of OCPs on the PS system are likely to be the main determinant for differences in hypercoagulability. The increased risk of VTE with third generation progesterone containing OCPs as compared to first or second generation progesterone is thought to be explained by a differential effect of progesterone on activated PC resistance [32] and is a well known phenomenon. Our study subjects were on the same OCP preparation, containing a second-generation progesterone norgestimate, yet developed variable thrombomodulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence based applications have now the widest distribution because these techniques have advantages over the absorption based approaches as the signal in the latter is disturbed by turbidity caused by coagulation events. It is now possible to perform measurements for the characterization of hereditary or acquired coagulation disturbances as well as for investigations into the influence of various medicines that affect the coagulation process beyond the time of clotting [9][10][11][12][13][14][15][16][17][18][19]. Hemker et al have reviewed further literature on such applications [20].…”
Section: Introductionmentioning
confidence: 99%